Do human resources practices influence organizational commitment? Evidence for the Brazilian retail sector - Pinho, Ana Paula Moreno; Silva, Clayton Robson Moreira da; Oliveira, Laís Vieira Castro; Oliveira, Evalda Rodrigues da Silva de; Barbosa, Daniel Araújo (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
This study aimed to investigate the influence of human resources practices on organizational commitment in its three dimensions. The research was carried out in a supermarket chain that operates in the Brazilian retail sector. Questionnaires were applied with the supermarket employees and the final sample is composed of 521 valid responses. Descriptive statistics, exploratory factor analysis and structural equation modeling were applied. The results evidenced that affective commitment is influenced by the work conditions, and the practice of competency-based performance appraisal influences continuance commitment, while the compensation and reward practice positively affects the normative commitment. This study contributes to the effectiveness of human resources practices and evidences the consistency of the application of the three-component model of commitment in Brazil.